Aplikasi Thread ”Fomo” Sebagai Budaya Imitasi dalam prespektif Studi Etnografi - Iin Soraya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The initial launch of Threads in Indonesia was proven to have reached 100 million users, many of whom downloaded the Threads application among Gen Z or teenagers who initially used Instagram, then downloaded the application and became Threads users. This is done just to join in, and not be left behind by other Instagram users. This kind of behavior is now known as Fear of Missing Out (FoMO). FoMO can be said to be a form of anxiety characterized by the desire to always know what other people are doing, as well as the fear of missing out on trends if you don't follow something that is viral, so this has given rise to a culture of imitation in generation Z. This research aims to find out Application of the "Fomo" thread as a culture of imitation from an ethnographic study perspective. The research method used is qualitative research. The research approach used in this research is phenomenology, using virtual ethnographic methods, by following the activities of Threads application users in cyberspace. Data collection techniques through observation, interviews, documentation and literature studies that support research. The research results obtained are that someone who has FoMO characteristics will feel anxious if they do not know the latest information from what is on social media. To fulfill these needs, individuals usually always require themselves to have trending social media, such as the Threads social media application. Threads users are Instagram account users who are advised to install the Threads application, so when the Threads application first appeared, many Instagram account users installed the Threads application.